Perianal lidocaine application during unsedated colonoscopy: A double-blind randomized controlled trial - Jiankun Wang; Yuwen Tao; Rui Wu; Lili Zhao; Li Liu; Zhining Fan; Wentao Fan (PLoS ONE, 2026)
Background and Aims nsedated colonoscopy is often associated with patient discomfort and may increase procedural difficulty for endoscopists. This study aimed to investigate the influence of perianal lidocaine application on the comfort level of patients and endoscopic operations during unsedated colonoscopy. Methods 122 patients aged 18–40 years were enrolled and randomly allocated to colonoscopy with 2% lidocaine (experiment group, n = 61) or normal saline (control, n = 61) smeared around the anus. The primary outcomes were anal pain score and abdominal pain score during and after colonoscopy, assessed using a visual analogue scale (VAS). Secondary outcomes included cecal intubation time, polyp detection rate, adenoma detection rate, and adverse events. Results There was no statistical difference between groups in terms of abdominal pain scores during unsedated colonoscopy. Abdominal pain scores after colonoscopy were significantly lower in the lidocaine group than in the saline group. (P < 0.001). However, the lidocaine group had significantly lower anal pain scores during and after colonoscopy (P < 0.001) and a shorter cecal intubation time (P < 0.001). Polyp and adenoma detection rates were higher in the lidocaine group (P < 0.05). Junior endoscopists achieved greater improvements in these outcomes compared to senior endoscopists. Conclusion Perianal application of lidocaine may reduce anal pain and may improve procedural efficiency during unsedated colonoscopy, particularly among junior endoscopists.